Opinion 2406: Elasmostethus dorsalis Jakovlev, 1876 (currently Elasmucha dorsalis): conditional precedence granted over Acanthosoma vicinum Uhler, 1861 (currently Elasmucha vicina) (Insecta, Heteroptera) - ICZN (Bulletin of Zoological Nomenclature, 2018)
The International Commission on Zoological Nomenclature has used its plenary power to grant conditional precedence to Elasmostethus dorsalis Jakovlev, 1876 over Acanthosoma vicinum Uhler, 1861 for a species of subsocial acanthosomatid bug from the Russian Far East.
Keywords: Nomenclature; taxonomy; Heteroptera; ACANTHOSOMATIDAE; Elasmucha; Elasmucha dorsalis; Elasmucha vicina; East Asia